Животные: независимое пособие для любознательных школьников (Большая детская энциклопедия, 2008)
Экземпляры: () / Инвентарный номер: 44455 / Цена: 184.08 / Сис.шифр: 28.6я2ср. 44455 / Авт.знак: Ж 67 / ББК: 28.6я2ср.